1984
DOI: 10.1093/ajcp/82.4.396
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prekallikrein, Factor XII, Antithrombin III, C1−-Inhibitor and α2-Macroglobulin in Critically III Patients with Suspected Disseminated Intravascular Coagulation (DIC)

Abstract: In nine patients with suspected disseminated intravascular coagulation (DIC) and five controls, the following analyses were performed on admission and 7-29 hours later: Routine coagulation studies (fibrinogen, platelet count, fibrin(ogen) degradation products, ethanol gelation, reptilase time, Factor V) providing a semiquantitative DIC score, prekallikrein (PK), Factor XII, antithrombin III (AT-III), C1(-)-inhibitor and alpha 2-macroglobulin. Significant correlations were found: PK or AT III with the DIC-score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…It has been previously demonstrated that plasma prekallikrein is transformed to kallikrein in a series of other pathophysiologic conditions such as septicemia, multitraumatized patients with multiple organ failure, and the adult RDS (1)(2)(3)(4)(5)17). On the basis of the present data it may therefore be tempting to speculate that RDS has some features in common with "posttraumatic" diseases such as those listed above (1)(2)(3)(4)(5).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been previously demonstrated that plasma prekallikrein is transformed to kallikrein in a series of other pathophysiologic conditions such as septicemia, multitraumatized patients with multiple organ failure, and the adult RDS (1)(2)(3)(4)(5)17). On the basis of the present data it may therefore be tempting to speculate that RDS has some features in common with "posttraumatic" diseases such as those listed above (1)(2)(3)(4)(5).…”
Section: Discussionsupporting
confidence: 48%
“…On the basis of the present data it may therefore be tempting to speculate that RDS has some features in common with "posttraumatic" diseases such as those listed above (1)(2)(3)(4)(5). It is known that RDS may be aggravated and precipitated by shock, hypothermia, and acidosis (26,27).…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, fulminant or acute DIC is characterized by both consumption coagulopathy and evidence of organ failure (Mü ller-Berghaus, 1989;Bick, 1995). Fulminant DIC is more frequent in ANLL than in solid tumour disease, and is relatively frequent in septicaemia (Lammle et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of AT III for the haemostatic balance is elucidated by the clinical observation that AT III plasma levels of less than 70-80% of normal are indicative of a thrombotic risk [3]. On the other hand, AT III may be reduced in the course of disseminated intravascular coagu lation [4][5][6], This would result in a reduced effectiveness of heparin treatment.…”
Section: Introductionmentioning
confidence: 99%